TATA HUKUM DI INDONESIA - Irvan Arisandi (Jurnal Syariah Hukum Islam, 2019)
The existing law system in Indonesia,is one of the law that has it’s own laws can be different from others Nations. Basically, the law system is the same as the law system, namely the way or system and argument. In my opinion that the Indonesian law system is the whole law system that apllies in Indonesia, both written law and unwritten, both currently in force and which is still expected today as result of government legislation as well as a from of recognition of the law that lives in the community. Introduction to the ruleof law in Indonesia is a branch of legal science.